Social Competence: Essence and Mechanisms of Formation in a Preschooler with Speech Impairment - M.M.Kakharova (Zien Journals, 2023)
The article discusses the issue of social competence, the essence and mechanisms of formation in a preschooler with speech impairment. The main attention is paid to identifying key competencies and areas of the competency-based approach in modern education
Keywords: competence; cognitive; emotional; behavioral